2018
DOI: 10.3390/children5070086
|View full text |Cite
|
Sign up to set email alerts
|

Methadone for Analgesia in Children with Life-Limiting Illness: Experience from a Tertiary Children’s Health Service

Abstract: Methadone has the potential to assist in the management of pain in children with life-limiting illness, but its use is limited by its complex pharmacokinetic profile and limited research on its use in children. This is a retrospective review of the use of methadone as an analgesic in 16 children with life-limiting illness. Efficacy, dosing and side effect profile were analysed. Fifteen (94%) patients had improvements in their analgesia with minimal observed adverse effects. Patients were either rapidly convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In a bicentric retrospective study ( 18 ), 16 children with a life-limiting disease (cancer, n = 12; neurological conditions, n = 3; cardiac diagnosis, n = 1) received methadone for incomplete analgesia on other high-potency opioids ( n = 9), adverse events from other opioids ( n = 6) and desire to use oral analgesic ( n = 3). Their mean age was 7.4 (1.3–16) years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a bicentric retrospective study ( 18 ), 16 children with a life-limiting disease (cancer, n = 12; neurological conditions, n = 3; cardiac diagnosis, n = 1) received methadone for incomplete analgesia on other high-potency opioids ( n = 9), adverse events from other opioids ( n = 6) and desire to use oral analgesic ( n = 3). Their mean age was 7.4 (1.3–16) years.…”
Section: Resultsmentioning
confidence: 99%
“…Both Davies et al ( 20 ) and Mott et al ( 18 ) reported data on methadone use in patients previously exposed to other high-potency opioid medications. In these cases, the strategies used for opioids to methadone conversion were specifically analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methadone toxicity in children can be deadly if antidote and supportive measures are not instituted in time [8]. Usual initial dose of methadone for moderate to severe pain relief in children ranged between 50 -100 µg/kg/dose [9][10][11][12]. In reported cases of acute methadone poisoning, dosage as low as 0.5 -1 mg/kg have been reported to potentially cause lifethreatening toxicity (i.e., respiratory depression) in children [13][14][15].…”
Section: Discussionmentioning
confidence: 99%